The Influence of Perceived Faculty Support on Psychological Health among Jordanian University Students - Shahrour, Ghada; Alqudah, Mohammad Abdulhameed; Al-Khayat, Amjad; Abu Obead, Kholoud (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aimed to assess the levels of stress, depression, and anxiety among Jordanian university students and whether faculty support plays a role in ameliorating student’s depression and anxiety. Methods: A cross-sectional study used a convenience sample of 18-25-year-old undergraduate students from five public and three private Jordanian universities. An online survey via EasyQuest was employed with prior university approvals. The survey link, including the consent form, was distributed through university websites, student union pages, and online student groups. The survey collected data on perceived stress, depression, anxiety, and student-faculty interaction from 1,067 university students (64.9% female). Results: The findings showed that Jordanian university students experience a substantial amount of stress, depression, and anxiety. While students’ stress increased their depression and anxiety, perceived faculty support had a significant ameliorating effect. Students scored their faculty interaction to be highest on the subscales of validity, respectful interactions, and approachability. On the other hand, having off-campus interaction with faculty and feeling a sense of connectedness had the lowest scores. Male university students expressed more depression and experienced less respectful interactions with university faculty than female students. Conclusion: The findings highlight the need to implement effective strategies to improve faculty interaction with university students and extend their role to support the psychological well-being of those students.